2021
DOI: 10.2131/jts.46.345
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion: a sensitive target for Pb exposure

Abstract: Pb exposure is a worldwide environmental contamination issue which has been of concern to more and more people. Exposure to environmental Pb and its compounds through food and respiratory routes causes toxic damage to the digestive, respiratory, cardiovascular and nervous systems, etc. Children and pregnant women are particularly vulnerable to Pb. Pb exposure significantly destroys children's learning ability, intelligence and perception ability. Mitochondria are involved in various life processes of eukaryote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 107 publications
0
21
0
Order By: Relevance
“…The adverse effects of Pb on cellular mitochondria is a critical mechanism of cytotoxicity induced by this heavy metal in various organs. 30,31 Pb could induce mitochondrial depolarization, ATP depletion, mitochondrial permeabilization, and release of cell death mediators form this organelle. 30,31 The current study showed a significant decrease in sperm ATP, mitochondrial depolarization, and mitochondrial dehydrogenases activity of Pb-exposed mice (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The adverse effects of Pb on cellular mitochondria is a critical mechanism of cytotoxicity induced by this heavy metal in various organs. 30,31 Pb could induce mitochondrial depolarization, ATP depletion, mitochondrial permeabilization, and release of cell death mediators form this organelle. 30,31 The current study showed a significant decrease in sperm ATP, mitochondrial depolarization, and mitochondrial dehydrogenases activity of Pb-exposed mice (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enhancing the sperm mitochondrial function is a strategy to improve its functionality indices. The adverse effects of Pb on cellular mitochondria is a critical mechanism of cytotoxicity induced by this heavy metal in various organs 30,31 . Pb could induce mitochondrial depolarization, ATP depletion, mitochondrial permeabilization, and release of cell death mediators form this organelle 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research, it was found that Pb exposure results in endoplasmic reticulum stress. Meanwhile, Pb exposure has also been shown to cause mitochondrial dysfunction [ 16 ]. Therefore, whether lead-induced ER stress is closely related to mitochondrial dysfunction is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%